Perempuan dalam Arus Politik Lokal: Studi Elektoral Keterpilihan Perempuan Pada Pemilihan Legislatif Tahun 2019 di Provinsi Jambi - Beriansyah, Alva; Muhammad, Hatta Abdi; Pratiwi, Cholillah Suci (Jurnal Noken: Ilmu-Ilmu Sosial, 2023)
This research examines the problems and electoral challenges of electing women from Jambi Province at the Central and Provincial Legislative Levels, which are still not representative of women. By using descriptive qualitative methods and combining the strengths of primary and secondary data. The findings in this study show that kinship with local political elites is one of the main political assets and strategies in contesting the 2019 Legislative Elections. The electability of existing women is still represented by women who utilize elements of family kinship with local political elites. Elected legislators who have political ties with local figures, such as local officials in the electoral district concerned, wives of local officials, children of local officials have an impact on the election of female legislators. This is because these local figures are well known by the wider community so that these figures will easily introduce their other relatives to participate in occupying other political positions. In fact, people who have loyalty to political figures who have been elected can immediately put their trust in new figures introduced by these political officials